2008
DOI: 10.1111/j.1553-2712.2008.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Optimal Dose of Intravenous Fat Emulsion for the Treatment of Severe Verapamil Toxicity in a Rodent Model

Abstract: Objectives: Recent animal studies have shown that intravenous fat emulsion (IFE) increases survival and hemodynamics in severe verapamil toxicity. However, the optimal dose of IFE is unknown. The primary objective was to determine the optimal dose of IFE based on survival in severe verapamil toxicity. Secondary objectives were to determine the effects on hemodynamic and metabolic parameters. The hypothesis was that there is a dose-dependent effect of IFE on survival until a maximum dose is reached.Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 17 publications
5
63
0
3
Order By: Relevance
“…Although there are no therapies that consistently reverse cardiovascular collapse caused by CCB poisoning, both high-dose insulin/euglycemia (HIE) therapy [2][3][4] and intravenous lipid emulsion (ILE) [5][6][7] have been shown to improve hemodynamics and survival following intravenous administration of verapamil in animals. On the other hand, while several case reports indicate amelioration of CCB-induced cardiotoxicity by the administration of ILE [8][9][10][11], others report no benefit [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no therapies that consistently reverse cardiovascular collapse caused by CCB poisoning, both high-dose insulin/euglycemia (HIE) therapy [2][3][4] and intravenous lipid emulsion (ILE) [5][6][7] have been shown to improve hemodynamics and survival following intravenous administration of verapamil in animals. On the other hand, while several case reports indicate amelioration of CCB-induced cardiotoxicity by the administration of ILE [8][9][10][11], others report no benefit [12].…”
Section: Introductionmentioning
confidence: 99%
“…After a 3-min stabilization period, each animal received either an ILE (20 % intravenous lipid emulsion, Baxter, Deerfield, IL, USA) 15 cm 3 /kg bolus over seven minutes or NS 15 cm 3 /kg bolus over 7 min. This ILE dose was selected based on previous rat models of ILE resuscitation which have successfully used doses ranging from 10 to 19 cm 3 /kg [4,6,7]. Two minutes after completion of the infusion and once MAP/HR returned to baseline, a bolus dose of intravenous epinephrine (15 μm/kg) was administered.…”
Section: Drug Exposurementioning
confidence: 99%
“…Following this trend of expanding utility, ILE has been shown to be efficacious in the emergency treatment of neurotoxicity and cardiotoxicity that results from a variety of cardiovascular and psychoactive drug classes. Animal studies have established benefit from ILE in various models of toxicity including verapamil [5,6], propranolol [7], amiodarone [8], and clomipramine [9]. Case studies have demonstrated successful use of ILE in haloperidol induced cardiac arrest [10], lamotrigine overdose [11], and in resuscitations of patients with combination ingestions of quetiapine/sertraline [12] and buproprion/lamotrigine [13].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid emulsion therapy has been studied for verapamil toxicity with impressive results in several animal models [4][5][6]. It has also been used to treat calcium channel antagonist toxicity in at least 20 published human cases, primarily involving verapamil and diltiazem [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%